Changes in the Transverse Dimension of the Maxillary Arch of 5-Year-Olds Born With UCLP Since the Introduction of Nationwide Guidance. (August 2022) - Molyneaux, Charlotte; Sherriff, Martyn; Wren, Yvonne; Ireland, Anthony; Sandy, Jonathan
Objective: To determine whether the transverse dimensions of the maxillary arch of 5-year-old children with unilateral cleft lip and palate (UCLP) have changed following centralization of cleft services in the United Kingdom. Design: Retrospective cross-sectional study. Setting: Digital analysis of UCLP maxillary dental casts. Participants: All available maxillary dental casts from 5-year-old participants of the Clinical Standards Advisory Group (CSAG, N = 114) and Cleft Care UK (CCUK, N = 175) studies. Interventions: Quantitative measurements of the intercanine width (ICW), intermolar width (IMW), and the distance from the midline to the greater and lesser side canine (GC/LC) and greater side and lesser side second primary molar (GE/LE). Degree measurements of the greater and lesser arch form angles, arch length, anterior palatal depth (APD), and posterior palatal depth were also measured. Main outcome: Differences between the transverse dimensions of the maxillary arch for the CSAG and CCUK cohorts. Results: In 5 (ICW, IMW, LC, LE, and APD) of the 11 measurements, there was a statistically significant difference between the CSAG and CCUK cohorts. In all of these, the CCUK values were greater than CSAG. Conclusions: There have been small but positive improvements for the transverse maxillary dimensions since centralization of the UK cleft service.